Papercrete and Recipanel as Wall Material: An Environmental Sustainability Review - Pangestika, Annisa Widya; Dewi, Ova Candra; Salsabila, Nisrina Dewi (Universitas Negeri Semarang, 2021)
This study aims to review the relation between papercrete and recipanel (wall materials from recycled paper) with indicators of material sustainability in environmental aspects. Recycling paper into wall material is one of the ways to overcome the increasing amount of paper waste in Indonesia. Waste recycling is related to the concept of sustainability, namely the triple bottom line of the concept of sustainability. A literature review of waste management, recycled paper, and recycled paper as wall material were conducted in terms of environmental sustainability. This study was conducted by integrating the theoretical understanding of waste, walls, wall material products from recycled paper and discussion of its impact in terms of the sustainability of recycled paper as alternative wall material. From this study, it was found that the relationship between the characteristics of papercrete and walls on the sustainability of recycled paper brought forward four positive values and two negative values. Meanwhile, the relation between recipanel and wall characteristics on the sustainability of recycled paper carries four positive values and two negative values. Thus, the recycled paper used as wall material with examples of papercrete and recipanel products may still be suitable for use as wall material in Indonesia. Suggestions resulted from this study that might be implemented in the future are to increase the durability of materials derived from recycled paper and to conduct studies that discuss wall materials derived from recycled paper from social and economic aspects in terms of sustainability.